Analisis Strategi Bisnis Pt. Xyz Untuk Berkembang Dalam Industri Saas - Christian Michael Budijanto dan Rina Adi Kristianti (Universitas Tarumanagara, 2019)
This research aims to analyze the strategies that have been pursued by PT. XYZ for long term strategy improvement and see opportunities that can be used to develop in the SAAS (software as a service) industry. Analytical method used to support research with three phases, ie Input Level, Match Stage, and Decision Stage. These three stages can help identify, evaluate and select strategies in PT XYZ. In this study compare products from PT. XYZ is Sales1CRM with competitors in the SAAS industry that provides CRM services. Competitors selected by authors include: HashMicro CRM, EspoCRM, and Barantum CRM as one of SAAS-based CRM service providers in Indonesia. Based on the results of the research which has been done by using three phases, that is, in the first phase of PT XYZ able to exploit existing opportunities and minimize its external threat, PT XYZ has more strength than its weakness factor, but PT. XYZ is still under HashMicro because the number of services provided is limited. While in the second stage, the SWOT matrix provides a SO strategy recommendation and in the SPACE matrix provides recommendations for aggressive strategy to continue to expand its market share, and the Internal-External Matrix recommends growth and build strategy. In the third stage, QSPM provides three alternative recommendations, namely, product development strategy in order to continue to grow following technology development and second alternative is market penetration strategy and horizontal integration.